Assisting liquid phase sintering of pure aluminum (Al) by the tin addition - Jamal, Nur Ayuni; Yusof, Farazila; Ahmad Nor, Yusilawati; Nordin, Norhuda Hidayah; Sulaiman, Suraya (IntechOpen, 2022)
In the present study, the addition of tin (Sn) to the pure Al system was done, and its effects on the morphology, density, and compressive yield strength of pure Al were analyzed systematically. In this context, the morphology of sintered Al revealed enhanced wettability and sintering response between Al particles with increased Sn content. Moreover, physical characteristics of sintered Al alloys demonstrated oxidation phenomenon (black color specimen) with the lowest Sn content of 1.5 weight percent (wt.%), in which a higher Sn content of 2 and 2.5 wt.% produced silver color specimens, implying a reduction in oxidation. Additionally, densification of sintered Al alloys was greatly promoted with increased Sn contents, suggesting effective wetting as confirmed by the previous morphological observations. Similarly, the compressive yield strength of sintered Al alloys improved with increased Sn content which might be due to the enhanced inter-particle contacts between Al particles and sufficient wetting by molten Sn. Based on the results obtained, the introduction of Sn powder at various contents improved the sintering response of pure Al powder by providing sufficient liquid-phase sintering. Therefore, the sintered Al alloys had enhanced the morphological, densification, physical characteristics, and compressive yield strength.